Application of Infrared Heating for Roasting Nuts - Hadi Bagheri (Journal of Food Quality)
Roasting is a key process in production of nuts. Improving the flavor and crispiness of texture in nuts is considered as a purpose of roasting, which increases the overall acceptance of the product. This review aims to introduce the infrared method as a new technique of roasting and evaluate the quality characteristics of some nuts after infrared roasting. Usually, the traditional roasting methods are time-consuming with high energy consumption and low production efficiency. One of the best ways to decrease roasting time and energy consumption is to provide heat by infrared (IR) radiation. However, the low penetration power of infrared radiation is one of the limitations of this method. The combination of infrared with other thermal methods can overcome this limitation. Studies have been done on roasting of nuts and other foods by different IR roasting methods such as IR, IR-hot air, and IR-microwave roasting methods. This paper reviews the effect of different IR roasting methods on the quality characteristics of roasted pistachio, peanut, hazelnut, almond, sunflower, soybean, and other food products. IR heating has been applied successfully to the roasting of some nuts. The use of infrared roasting has several advantages in comparison with traditional convective roasting methods. According to the results of most of these studies, the combination of infrared with other thermal methods to roast nuts has distinctly improved the potential of the technology as compared to the IR roasting alone.